EXPLORING NETWORKS AND COMMUNITIES: A CASE STUDY OF THE SUPPORTERS AND CRITICS FACEBOOK PAGES OF THE PHILIPPINE PRESIDENT - Tamanal, Juvy Lou; Lim, Jongsoo (PEOPLE: International Journal of Social Sciences, 2019)
This paper provides the current Philippine president’s supporters and critics Facebook pages on social media networks’ description and analyses of their SNSs dataset using NodeXL program. There are three main focuses of the study: (1) implications of the demographic differences of both page networks in terms of age, location and political affiliation, (2) comparative data analyses of the difference in the connected vertices/nodes (e.g., density, diameter, and connected components) of the two opposing networks, and finally, (3) identifying the network actors, the “who” play the roles of the main speakers, mediators and influencers in a social network structure. Results show that the networks’ description for the supporters’ page group has denser connected components compared to the critics’ page. Actors on both networks like the main users, mediators and influencers are media bloggers, social media users and the overseas foreign workers (OFWs). The overall findings of this study showed that the two networks have strong signs of real-life communities in a social networking space.